Systematic framework for design of biomass energy systems: Addressing criticality via redundancy allocation - Andiappan, Viknesh (Animo Repository, 2017)
A biomass energy system (BES) consists of highly integrated process units within a network. Via process integration, such system can achieve higher thermodynamic efficiency levels and economic performance as compared to conventional stand-alone systems. However, such benefits may not be realised if an energy system is not equipped to cope with failure of its component process units. A failure event can cause "ripple effects" to propagate throughout the BES and disrupt its overall performance. To address this, designers often allocate additional or redundant process units for the entire BES. However, this approach requires high capital investment; thus, redundancy allocation for the entire BES would not be possible. An appropriate resolution for this issue would be to identify the most critical process unit in the BES prior to allocating equipment redundancy. In this respect, this work presents a decision making framework for designing BES by addressing criticality of process units via redundancy allocation. The first stage of the framework consists of criticality analysis approach based on input-output (I-O) analysis. The criticality analysis identifies the most crucial process unit by quantifying the effect of a component's disruption within the BES. After identifying the most critical process unit, the second stage of the framework allows designers to systematically allocate equipment redundancy based on their budget restrictions via k-out-m system modelling or process intensification. To demonstrate the proposed framework, a palm-based BES case study is solved. © 2017, AIDIC Servizi S.r.l.